Community Empowerment and Strengthening of Entrepreneurial Practices: Case Study from Traditional Snack Souvenir Business of Mrs. Mumun in Kopo Village, Inner Cisarua, Bogor Regency, Indonesia - Wahyudi, Ade; Supriyadi, Rendinanda Prakoso; Defano, Muhammad Nofal; Haliza, Elshiva Putri; Febriyana, Anzhani Sahar; Zakaria, Dava Ahmad; Rahmah, Fakhira Nur; Putri, Tasya Amelia (Manunggal Halim Jaya, 2025)
In this community service activity, we visited the traditional snack souvenir business of Bu Mumun in Kopo Village, Cisarua Dalam, Bogor. Based on the methods we used in the community service activity, such as observation and interview methods, socialization, and practices. However, Mumun's production still has some packaging and marketing limitations. Regarding packaging, Bu Mumun only uses PE (polyethylene) plastic to package her snacks. In contrast, in the marketing aspect, Bu Mumun only relies on word-of-mouth marketing, so we help in the production by adding a logo and replacing PE packaging with ziplock packaging to make the product more durable. While in the marketing aspect, we help make Google Maps and install banners and acrylics. We hoped that the results of our activities would help Bu Mumun's business unit grow even more.